PRICING MECHANISM OF PROCESSED WOOD IN VARIOUS QUALITY LEVELS AT THE COT KEUENG SETTLEMENT MILL FROM THE PERSPECTIVE OF AKAD AL-BA'I - Riska (JURISTA: Jurnal Hukum dan Keadilan, 2018)
In conducting a sale and purchase transaction, there are certain terms and conditions to make the sale and purchase transaction valid, in the Al-Ba'i contract there is a price determination made by the seller and agreed by both parties, namely the seller and the buyer. In determining a balanced price, a price mechanism is needed so that the price set does not exceed the limit, and does not take a large amount of profit. Because, by setting a good selling price, it can retain buyers because price is one of the most important in marketing. This study examines the pricing mechanism of processed wood at the Cot Keueng refinery in various quality levels. This research uses descriptive analysis method with a qualitative approach, with data collection techniques by means of: 1) interview; 2) observation; 3) documentation; and 4) observation. The results showed that: first, the pricing mechanism that occurs in Cot Keung panglong has different pricing between one panglong and another. Second, pricing in the first panglong includes initial costs, production costs, and employee salary costs. While the second pricing mechanism is almost the same as the pricing in the first panglong, only in the second panglong it does not include employee salary costs. The pricing calculation pattern is based on the costs incurred during the production process, which includes the costs of the initial purchase price of wood, the products used, and the tools needed during the furniture working process. Third, the above pricing mechanism is permissible according to Islamic law, because Islamic law does not determine a specific mechanism in setting prices.